2020
DOI: 10.1093/g3journal/jkaa003
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analyses of theDrosophilapupal eye

Abstract: Tissue function is dependent on correct cellular organization and behavior. As a result, the identification and study of genes that contribute to tissue morphogenesis is of paramount importance to the fields of cell and developmental biology. Many of the genes required for tissue patterning and organization are highly conserved between phyla. This has led to the emergence of several model organisms and developmental systems that are used to study tissue morphogenesis. One such model is the Drosophila melanogas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 233 publications
(246 reference statements)
0
1
0
Order By: Relevance
“…Alternatively, it is conceivable that these proteins have other, yet to be identified, functions in the Drosophila eye that are required upon increased lipid unsaturation. Interestingly, the expression of genes that are associated with muscle development has been detected in the pupal eye, and Troponin I/Wings up A additionally controls the proliferation of epithelial cells as well as the localization of apical-basal polarity signaling proteins . Third, the upregulation of muscle-related proteins could be due to a yet to be identified mechanistic link between lipid unsaturation and increased muscle protein expression that co-occur at low temperatures; we previously showed that at temperatures below 15 °C, Drosophila alter their dietary preference from yeast to plant material in laboratory foods but also in the wild, which provides unsaturated fatty acids that improve membrane fluidity and motor functions .…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it is conceivable that these proteins have other, yet to be identified, functions in the Drosophila eye that are required upon increased lipid unsaturation. Interestingly, the expression of genes that are associated with muscle development has been detected in the pupal eye, and Troponin I/Wings up A additionally controls the proliferation of epithelial cells as well as the localization of apical-basal polarity signaling proteins . Third, the upregulation of muscle-related proteins could be due to a yet to be identified mechanistic link between lipid unsaturation and increased muscle protein expression that co-occur at low temperatures; we previously showed that at temperatures below 15 °C, Drosophila alter their dietary preference from yeast to plant material in laboratory foods but also in the wild, which provides unsaturated fatty acids that improve membrane fluidity and motor functions .…”
Section: Discussionmentioning
confidence: 99%